2002
DOI: 10.1590/s1413-86702002000500002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host-related factors on the intensity of liver fibrosis in patients with chronic hepatitis C virus infection

Abstract: There is increasing interest in the identification of factors associated with liver disease progression in patients infected with hepatitis C virus (HCV). We assessed host-related factors associated with a histologically advanced stage of this disease and determined the rate of liver fibrosis progression in HCV-infected patients. We included patients submitted to liver biopsy, who were anti-HCV and HCV RNA positive, who showed a parenteral risk factor (blood transfusion or intravenous drug use), and who gave i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…In the current study, all groups showed insignificant difference as regard to age, and sex as fibrosis progression was influenced by duration of infection and the age at time of infection [15].…”
Section: Discussioncontrasting
confidence: 47%
“…In the current study, all groups showed insignificant difference as regard to age, and sex as fibrosis progression was influenced by duration of infection and the age at time of infection [15].…”
Section: Discussioncontrasting
confidence: 47%
“…Patients infected at an older age or those with a longer disease course present with more advanced stages. 11 , 12 , 13 , 14 Several investigations have demonstrated rapid disease progression among patients infected at older ages, particularly in studies of patients enrolled with early-stage fibrosis (F0, F1), where progression to advanced fibrosis was more common among patients older than 40–50 years. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…3,25,26 One study has suggested that antioxidant defense mechanism deteriorates with age, and leaves the liver vulnerable to oxidative stress. 27 Our finding was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%